Bi-salpingo Colonic Fistula Report of Both Fallopian Tubes Fistulizing with Sigmoid Diverticulum with Literature Review - Nawal S. Al Sinani (Journal of King Abdulaziz University: Medical Sciences, 2023)
Fistulous communication between the colon and female adnexal structure rarely occurs. The rarity of the condition reflects that only few cases have been reported in the literature, however, the bisalpingocolonic fistulae have never been reported. A case study of a 28-years-old woman with primary infertility of four years duration diagnosed with bilateral salpingocolonic fistulae by hysterosalpingography (HSG), which was performed as part of the routine work-up of infertility showed; contrast filed both tubes till fimbrial ends then joined diverticulum in sigmoid colon with opacification down to the rectum. Laparoscopic salpingectomy and closure of fistula were done. The patient was referred to the assisted conception unit and underwent two in vitro fertilizations. An embryo transfer resulted on the second attempt in pregnancy and a normal healthy full term baby. In conclusions, Salpingocolonic fistula is a very rare disease and closure of the fistula is the treatment of choice with the need to IVF assisted conception.